THE INFLUENCE OF SELF-REGULATED LEARNIG AND SELF-AWARENESS ON LEARNING OUTCOMES IN ECONOMIC SUBJECTS (Survey of Class XI IPS Students at SMA Negeri 1 Cikatomas Academic Year 2021/2022) - Alvian Septia Agustina; Ati Sadiah; Raden Roro Suci Nurdianti (JOURNAL SAINS STUDENT RESEARCH, 2024)
The research aims to determine the effect of self-regulated learning and self-awareness on learning outcomes in economics subjects. The research method uses quantitative with an explanatory survey design. The population of Class XI IPS students at SMA Negeri 1 Cikatomas for the 2021/2022 academic year is 240 people. The sampling technique used was saturated sampling, so the total sample taken was 240 people. Data collection techniques in this research used questionnaires, statistical tests used multiple linear regression and coefficient of determination, and the hypothesis tests used were partial tests (t tests) and simultaneous tests (f tests). The research results show that self-regulated learning and self-awareness have an influence on student learning outcomes partially or simultaneously.